Enhancement of hydrogen production performance of novel perovskite LaNi0.4Al0.6O3‐δ supported on MOF A520‐derived λ‐Al2O3. (27th June 2022) - Shen, Qiuwan; Shao, Zicheng; Cai, Zhongwen; Yan, Min; Yang, Guogang; Li, Shian
Summary: Methanol steam reforming (MSR) is a promising method for hydrogen production from renewable energy. The effect of λ‐Al2 O3 support derived from metal‐organic frameworks (MOFs) aluminum fumarate (A520) on the performance and stability of LaNi0.4 Al0.6 O3‐δ for MSR is investigated. Results demonstrate that compared with LaNi0.4 Al0.6 O3‐δ, LaNi0.4 Al0.6 O3‐δ /λ‐Al2 O3 can achieve complete conversion of methanol and excellent thermal stability due to the higher SBET and strong interaction between the metal components and λ‐Al2 O3 . Characterization results indicate that the LaNi0.4 Al0.6 O3‐δ /λ‐Al2 O3 catalyst, which was not successfully reduced due to its robust structure, still has active sites for the MSR reaction. This characteristic of the catalyst has the potential to be applied for onboard in‐situ hydrogen production, because it can shorten the time of hydrogen reduction process. Furthermore, the effects of catalytic temperature, feed water‐methanol ratio, and liquid hourly space velocity on performance of LaNi0.4 Al0.6 O3‐δ /λ‐Al2 O3 are studied in detail and the optimal conditions ​​are determined and applied for stability tests. Abstract : A new strategy of supporting perovskite oxides on λ‐Al2 O3 is proposed first in this paper. The synthesized novel LaNi0.4 Al0.6 O3‐δ /λ‐Al2 O3 showed better performance with a higher SBET and methanol conversion rate. The 100% of methanol conversion and excellent thermal stability due to the strong interaction between the metal components and the support, which promotes the high dispersion of LaNi0.4 Al0.6 O3‐δ .